A composite flocculant for simultaneously removing microplastics and emerging pollutants and a preparation method thereof

A composite flocculant was prepared by synergistic action of silane coupling agent with aluminum and iron salts, which solved the problem of low removal efficiency of existing flocculants for microplastics and new pollutants, and achieved simultaneous and efficient removal of microplastics and new pollutants. It is suitable for surface water, deep treatment of urban sewage and protection of drinking water sources.

CN122324955APending Publication Date: 2026-07-03HUNAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610520992.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-04-20
Publication Date
2026-07-03

Smart Images

  • Figure CN122324955A_ABST
    Figure CN122324955A_ABST
Patent Text Reader

Abstract

The application provides a composite flocculant for synchronously removing microplastics and new pollutants and a preparation method thereof, the method comprises the following steps: after hydrolysis and purification of a silane coupling agent TPODAC, the TPODAC is compounded and activated with aluminum salt and iron salt in a specific ratio under the condition that the pH value is 3.0-3.5, and then the composite flocculant is obtained through aging. By optimizing the key parameters such as the amount-of-substance ratio of metal elements (Al+Fe) to silicon, the aluminum-iron ratio and the activation pH value, the synergistic removal capacity of the material to multiple types of pollutants is significantly improved. The flocculant performs excellently under the condition that the pH value of the conventional water body is 7-8: 10 mg / L of the flocculant can be added to efficiently remove microplastics and conventional pollutants; 30 mg / L of the flocculant can be added to remove more than 75% of various new pollutants (tetracycline, diclofenac and ibuprofen). The application has the advantages of controllable process, wide applicability, high removal efficiency and the like, and is suitable for the synchronous advanced treatment of microplastics and new pollutants in water bodies.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of water treatment materials technology, specifically relating to a composite silicon-aluminum-iron-based flocculant and its preparation method for simultaneously and efficiently removing microplastics and typical new pollutants (diclofenac, ibuprofen, tetracycline) from water. Background Technology

[0002] Plastic pollution has become a global environmental challenge. Waste plastics break down and age in the environment, forming microplastic particles smaller than 5 mm. These particles are not only ecotoxicous themselves, but also, due to their hydrophobicity and large specific surface area, act as carriers of other pollutants in water bodies, particularly exhibiting a strong bioaccumulation effect on emerging pollutants such as antibiotics and nonsteroidal anti-inflammatory drugs. This complex pollution formed by microplastics and dissolved emerging pollutants presents far more complex environmental behaviors and ecological risks than that of a single pollutant, seriously threatening aquatic ecosystems and drinking water safety.

[0003] Currently, technologies for treating microplastics, such as flotation separation and membrane filtration, are either too costly or difficult to apply on a large scale in water treatment. Flocculation and sedimentation, as a core process in water treatment, offers advantages such as low operating costs and ease of operation. Traditional inorganic flocculants (such as polyaluminum chloride and polyferric sulfate) are effective at removing colloidal particles and some phosphorus, but their removal efficiency is limited for electrically neutral or hydrophobic microplastic particles, as well as structurally stable, hydrophilic, and soluble new pollutants. For dissolved new pollutants with specific functional groups, traditional inorganic flocculants have almost no active removal capability. Current research and technologies mostly target single pollutants (such as removing only microplastics or antibiotics), lacking methods for simultaneously and efficiently removing microplastics and enriched soluble new pollutants. When microplastics and new pollutants coexist, their interactions interfere with the flocculation process, reducing removal efficiency.

[0004] Therefore, developing a novel flocculant capable of addressing the combined pollution of microplastics and new pollutants in water bodies and possessing broad-spectrum removal capabilities is of urgent practical need and significant application value, especially in applications such as surface water, advanced urban sewage treatment, and drinking water source protection. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of existing flocculants, such as low removal efficiency and narrow applicability for microplastics and certain new pollutants. It provides a composite flocculant (VAC) with a simple preparation method, low cost, and the ability to simultaneously and efficiently remove microplastics (represented by polystyrene) and various new pollutants (tetracycline, diclofenac, ibuprofen) from water, along with its preparation method. This invention utilizes the synergistic effect of silane coupling agents with aluminum and iron salts to construct a composite flocculant with adsorption, charge neutralization, and bridging functions, thereby solving the existing technical problems.

[0006] To achieve the above objectives, the present invention provides a method for preparing a composite flocculant for simultaneously removing microplastics and new pollutants, comprising the following steps: (1) Precursor hydrolysis: The silane coupling agent dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride was dissolved in a mixed solution composed of ethanol, concentrated hydrochloric acid and deionized water to carry out the hydrolysis reaction, and a silanol active solution was obtained. (2) Dialysis purification: The silanol active solution obtained in step (1) is subjected to dialysis to remove small molecule byproducts and obtain purified silanol active solution. (3) Combination and activation: Add a metal salt solution containing aluminum and iron to the purified silanol active solution obtained in step (2), and then adjust the pH of the system to 3.0~3.5 with an alkaline solution to initiate the synergistic condensation reaction of silanol and metal ions to obtain the reaction solution; (4) Aging: After stirring the reaction solution obtained in step (3), let it stand for aging to obtain the composite flocculant.

[0007] Furthermore, in step (1), the volume concentration of the silane coupling agent TPODAC is 2%, the composition of ethanol and concentrated hydrochloric acid in the mixed solution is 78% and 0.02% respectively, and the dissolution / stirring rate is 200-250 r / min.

[0008] Furthermore, in step (2), the dialysis treatment specifically involves placing the silanol active solution in the pretreated dialysis membrane and performing dialysis in a dilute hydrochloric acid solution with a pH of 2 to 2.5 for a total dialysis time of 8 to 10 hours, during which the dialysis solution is replaced 4 to 6 times.

[0009] Furthermore, the pretreatment method for the dialysis membrane includes: boiling it in a 2% sodium bicarbonate solution and a 1 mmol / L EDTA solution for 8-15 minutes respectively, and then rinsing it with deionized water.

[0010] Furthermore, in step (3), the total amount of aluminum and iron in the aluminum and iron metal salt solution is 10~15:1 with the molar ratio of silicon in the purified silanol active solution, and the molar ratio of aluminum to iron is 1.5~2:1. The total concentration of metal ions in the mixed solution is controlled to be no more than 0.05 mol / L.

[0011] Furthermore, in step (3), the metal salt solutions containing aluminum and iron are aluminum chloride and ferric chloride, respectively; the alkaline solution is a sodium hydroxide solution with a concentration of 0.5 mol / L.

[0012] Furthermore, in step (4), the stirring reaction is magnetic stirring, with a stirring rate of 150~200 rpm, a temperature of 18~22 ℃, and a stirring time of 10~15h.

[0013] Furthermore, in step (4), the static aging temperature is 18-22 ℃ and the static time is 10-15 h to obtain the composite flocculant.

[0014] Furthermore, the new pollutants include diclofenac, ibuprofen, and tetracycline.

[0015] The present invention also provides a composite flocculant prepared by the above preparation method, which is used for the synergistic removal of microplastics and conventional nutrients, wherein the dosage of the composite flocculant is 10~20 mg / L. For enhanced removal of new pollutants, the dosage of the composite flocculant is 30-50 mg / L.

[0016] The beneficial effects of this invention are: This invention overcomes the shortcomings of existing technologies, such as difficulty in precisely controlling hydrolysis-condensation reactions, disordered active sites, and inability to simultaneously remove complex pollutants, through a strategy of "dialysis purification + experimental optimization + multi-mechanism synergy." It provides a novel composite flocculant with controllable process and broad-spectrum, high-efficiency removal capabilities. The composite flocculant prepared by this invention is used to remove microplastics and new pollutants from wastewater and natural water bodies. During application, the surface-crosslinked metal polymers are removed via Al... 3+ Fe 3+ Hydrolysis generates hydroxyl complexes, whose long internal carbon chains enhance charge neutralization and adsorb hydrophobic pollutants through quaternary ammonium groups and hydrophobic interactions.

[0017] This invention achieves broad-spectrum and efficient removal: The composite flocculant VAC prepared in this invention exhibits excellent broad-spectrum removal capabilities under conventional water pH conditions (7-8). At a dosage of 10 mg / L, the removal rate of microplastic polystyrene particles in water can reach over 90%; the removal rates of nitrate nitrogen, total phosphorus, and total nitrogen in simulated urban wastewater all exceed 85%. This invention also achieves deep removal of novel pollutants: Under the same pH conditions (7-8), increasing the VAC dosage to 30 mg / L achieves a removal rate exceeding 75% for typical novel pollutants tetracycline, diclofenac, and ibuprofen, realizing effective deep removal of dissolved organic micropollutants.

[0018] Significant synergistic effect: When VAC is added to water, the aluminum-iron hydroxyl complexes anchored in the silicon-oxygen network release high-density positive charges, rapidly destabilizing negatively charged microplastics and diclofenac. Simultaneously, the covalently linked long carbon chains capture hydrophobic microplastics such as polystyrene through hydrophobic interactions, while quaternary ammonium groups provide permanent positive charges and regulate the hydrophilic-hydrophobic balance. After the destabilized pollutants are captured by the active sites on the VAC surface, the silicon-oxygen-aluminum-iron covalent network self-assembles into three-dimensional large-sized flocs, which are then encapsulated and settled by a net-like trapping and sweeping mechanism. These four stages are synergistically triggered on the same particle: charge neutralization promotes hydrophobic adsorption, hydrophobic adsorption enhances floc capture, and net-like trapping and sweeping ensure complete separation, achieving a synergistic effect of "1+1>2".

[0019] The preparation process of this invention is controllable and environmentally friendly: the preparation process is based on a controllable hydrolysis-condensation reaction, and the bond parameters are optimized through orthogonal experiments to ensure the reproducibility and stability of the product performance. The raw materials are widely available, the preparation process requires no complex equipment, and the final product has a low concentration of residual metal ions after use, resulting in minimal environmental risk and aligning with the development concept of green chemistry.

[0020] In addition to the objectives, features, and advantages described above, the present invention has other objectives, features, and advantages. The invention will now be described in further detail with reference to the accompanying drawings. Attached Figure Description

[0021] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings: Figure 1 This is a TEM image of the composite flocculant VAC obtained in Example 1 of the present invention; Figure 2 The graph shows the removal effect of microplastics, total nitrogen, nitrate nitrogen and total phosphorus in wastewater under different flocculant dosages of the composite flocculant VAC obtained in Example 1 of the present invention. Figure 3 The graph shows the removal effect of diclofenac, ibuprofen, and tetracycline in wastewater under different flocculant dosages of the composite flocculant VAC obtained in Example 1 of this invention. Detailed Implementation

[0022] The present invention will now be further described with reference to the accompanying drawings. Those skilled in the art will be able to implement the present invention based on these descriptions. Furthermore, the embodiments of the present invention described below are generally only some, not all, of the embodiments of the present invention. Therefore, all other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort should fall within the scope of protection of the present invention. Example 1:

[0023] (1) Precursor hydrolysis: The silane coupling agent dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride (TPODAC) was dissolved in a mixed solution consisting of ethanol, concentrated hydrochloric acid, and deionized water, wherein the volume concentration of TPODAC was 2%, and the compositions of ethanol and concentrated hydrochloric acid in the mixed solution were 78% and 0.02%, respectively. The solution was magnetically stirred at room temperature for 24 hours to obtain a clear hydrolysate.

[0024] (2) Dialysis purification: The hydrolysate was injected into a pretreated dialysis membrane (molecular weight cutoff of 1000 Da). The pretreatment method of the dialysis membrane was as follows: it was boiled in a 2% sodium bicarbonate solution and a 1 mmol / L EDTA solution for 10 minutes, and then thoroughly cleaned with deionized water. The hydrolysate was placed in the pretreated dialysis membrane and dialyzed in a dilute hydrochloric acid solution with a pH of 2.2 for a total dialysis time of 9 hours, during which the dialysis solution was replaced 5 times to completely remove small molecule byproducts such as methanol generated by hydrolysis.

[0025] (3) Combination and Activation: After dialysis, the silanol active solution in the bag was transferred to a beaker. Based on the preset (Al+Fe):Si molar ratio of 10 and Al:Fe molar ratio of 2, the required masses of AlCl3·6H2O and FeCl3·6H2O were calculated. After dissolving in a small amount of deionized water, the solution was slowly added to the silanol solution with stirring. The total concentration of metal ions in the mixed solution was controlled to be no higher than 0.05 mol / L. Subsequently, with continuous stirring, the pH of the system was slowly and precisely adjusted to the set activation pH of 3.5 using a 0.5 mol / L NaOH solution to initiate the synergistic condensation reaction between the silanol and metal ions.

[0026] (4) Aging: After adjusting the pH, the mixture from step (3) is magnetically stirred for 12 hours at room temperature. Then, stirring is stopped and the mixture is allowed to stand at room temperature for 12 hours to obtain composite flocculant VAC-1.

[0027] like Figure 1 The image shown is a TEM image of the composite flocculant VAC obtained in Example 1 of this invention, with a scale bar of 50 nm. The surface of the composite flocculant consists of organic-inorganic hybrid nanoparticles modified with a silicon-aluminum-iron metal polymer. Example 2:

[0028] (1) Precursor hydrolysis: The silane coupling agent dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride (TPODAC) was dissolved in a mixed solution consisting of ethanol, concentrated hydrochloric acid, and deionized water, wherein the volume concentration of TPODAC was 2%, and the compositions of ethanol and concentrated hydrochloric acid in the mixed solution were 78% and 0.02%, respectively. The solution was magnetically stirred at room temperature for 24 hours to obtain a clear hydrolysate.

[0029] (2) Dialysis purification: The hydrolysate was injected into a pretreated dialysis membrane (molecular weight cutoff of 1000 Da). The pretreatment method of the dialysis membrane was as follows: it was boiled in a 2% sodium bicarbonate solution and a 1 mmol / L EDTA solution for 10 minutes, and then thoroughly cleaned with deionized water. The hydrolysate was placed in the pretreated dialysis membrane and dialyzed in a dilute hydrochloric acid solution with a pH of 2.2 for a total dialysis time of 9 hours, during which the dialysis solution was replaced 5 times to completely remove small molecule byproducts such as methanol generated by hydrolysis.

[0030] (3) Combination and Activation: After dialysis, the silanol active solution in the bag was transferred to a beaker. Based on the preset (Al+Fe):Si molar ratio of 15 and Al:Fe molar ratio of 1, the required masses of AlCl3·6H2O and FeCl3·6H2O were calculated. After dissolving in a small amount of deionized water, the solution was slowly added to the silanol solution with stirring. The total concentration of metal ions in the mixed solution was controlled to be no higher than 0.05 mol / L. Subsequently, with continuous stirring, the pH of the system was slowly and precisely adjusted to the set activation pH of 3.0 using a 0.5 mol / L NaOH solution to initiate the synergistic condensation reaction between the silanol and metal ions.

[0031] (4) Aging: After adjusting the pH, the mixture from step (3) is magnetically stirred for 12 hours at room temperature. Then, stirring is stopped and the mixture is allowed to stand at room temperature for 12 hours to obtain composite flocculant VAC-2. Example 3:

[0032] (1) Precursor hydrolysis: The silane coupling agent dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride (TPODAC) was dissolved in a mixed solution consisting of ethanol, concentrated hydrochloric acid, and deionized water, wherein the volume concentration of TPODAC was 2%, and the compositions of ethanol and concentrated hydrochloric acid in the mixed solution were 78% and 0.02%, respectively. The solution was magnetically stirred at room temperature for 24 hours to obtain a clear hydrolysate.

[0033] (2) Dialysis purification: The hydrolysate was injected into a pretreated dialysis membrane (molecular weight cutoff of 1000 Da). The pretreatment method of the dialysis membrane was as follows: it was boiled in a 2% sodium bicarbonate solution and a 1 mmol / L EDTA solution for 10 minutes, and then thoroughly cleaned with deionized water. The hydrolysate was placed in the pretreated dialysis membrane and dialyzed in a dilute hydrochloric acid solution with a pH of 2.2 for a total dialysis time of 9 hours, during which the dialysis solution was replaced 5 times to completely remove small molecule byproducts such as methanol generated by hydrolysis.

[0034] (3) Combination and Activation: After dialysis, the silanol active solution in the bag was transferred to a beaker. Based on the preset (Al+Fe):Si molar ratio of 12 and Al:Fe molar ratio of 1.8, the required masses of AlCl3·6H2O and FeCl3·6H2O were calculated. After dissolving in a small amount of deionized water, the solution was slowly added to the silanol solution with stirring. The total concentration of metal ions in the mixed solution was controlled to be no higher than 0.05 mol / L. Subsequently, with continuous stirring, the pH of the system was slowly and precisely adjusted to the set activation pH of 3.2 using 0.5 mol / L NaOH solution to initiate the synergistic condensation reaction between silanol and metal ions.

[0035] (4) Aging: After adjusting the pH, the mixture from step (3) is magnetically stirred for 12 hours at room temperature. Then, stirring is stopped and the mixture is allowed to stand at room temperature for 12 hours to obtain composite flocculant VAC-3.

[0036] Performance verification: Using the VAC prepared in Example 1, we investigated its removal effect on various pollutants at different dosages in normal water bodies at pH (7.5-8.0).

[0037] Removal of microplastics and conventional pollutants: A simulated wastewater containing polystyrene microplastics (10 mg / L), nitrate nitrogen (20 mg / L), total nitrogen (25 mg / L), and total phosphorus (5 mg / L) was prepared and the pH was adjusted to 7.5. A 500 mL water sample was taken and tested according to the standard flocculation procedure (rapid stirring 300 rpm / 2 min, slow stirring 50 rpm / 15 min, settling for 30 min). The dosage of VAC-1 was varied (5, 10, 15, 20, 25, 30 mg / L), and the concentration of each pollutant in the supernatant was measured. The removal rate was calculated, and the results are shown in Table 1.

[0038] Table 1. Effect of VAC-1 dosage on the removal of microplastics and conventional pollutants As shown in Table 1, VAC-1 exhibits extremely strong removal capabilities for microplastics, achieving a removal rate exceeding 90% at a dosage of 10 mg / L, peaking at 95.5% at 20 mg / L. It also demonstrates significant removal efficiency for total phosphorus, with the removal rate continuously increasing with dosage, reaching as high as 97.6% at 30 mg / L. Regarding nitrogen removal, the nitrate nitrogen removal rate steadily increases with dosage, while the total nitrogen removal rate remains at a high level (>83%). Considering both efficiency and cost-effectiveness, a VAC-1 dosage of 10-20 mg / L is recommended for the synergistic removal of microplastics and conventional nutrients.

[0039] Figure 2 The study demonstrates the changes in removal rates of microplastics and conventional pollutants under different VAC-1 dosages. Experimental data show that the microplastic removal rate peaked at 95.55% at 20 mg / L, and decreased slightly with further increases in dosage; the total phosphorus removal rate continuously increased with increasing dosage, reaching as high as 97.66% at 30 mg / L; the nitrate nitrogen removal rate steadily increased from 32.90% to 86.80%; and the total nitrogen removal rate remained stable above 83%. Considering both efficiency and economy, a VAC-1 dosage of 10–20 mg / L is recommended.

[0040] Removal of new pollutants: Mixed simulated wastewater containing 10 mg / L each of tetracycline, diclofenac, and ibuprofen was prepared and the pH was adjusted to 8.0. The same flocculation program was used to investigate the removal effects of VAC-1 dosage (10, 20, 30, 40, 50 mg / L) on the three drugs. The results are shown in Table 2.

[0041] Table 2. Effect of VAC-1 dosage on the removal of new pollutants Table 2 shows that VAC-1 exhibits good removal capabilities for all three new pollutants, and the removal rate increases with increasing dosage. At a dosage of 30 mg / L, the removal rates for diclofenac, tetracycline, and ibuprofen reached 79.8%, 71.1%, and 69.4%, respectively, all exceeding or approaching 70%. When the dosage is increased to 50 mg / L, the removal rate can be further improved to over 80%. This indicates that VAC-1 is suitable for the advanced treatment of dissolved organic micropollutants.

[0042] Figure 3 The removal rates of three new pollutants were observed under different VAC-1 dosages. Experimental data showed that the removal rates of diclofenac, tetracycline, and ibuprofen all increased continuously with increasing dosage. For enhanced removal of the new pollutants, a VAC-1 dosage of 30-50 mg / L is recommended. The performance of VAC-2 prepared in Example 2 and VAC-3 prepared in Example 3 is similar to that of VAC-1 prepared in the examples, and will not be described further here.

[0043] Comparative Example 1: (Dialysis purification step omitted) In Comparative Example 1, step (2) dialysis purification was omitted during the preparation process. That is, the precursor was hydrolyzed and then directly compounded and activated. The remaining steps were exactly the same as in Example 1.

[0044] Preparation steps: (1) Precursor hydrolysis is the same as in Example 1; dialysis purification is omitted, and the hydrolysate is not subjected to dialysis treatment; (2) Compounding and activation: A mixed solution of aluminum chloride and ferric chloride is directly added to the unpurified hydrolysate, controlling (Al+Fe):Si=10:1, Al:Fe=2:1, and the pH is adjusted to 3.5 with 0.5 mol / L NaOH; (3) Maturation is the same as in Example 1. The obtained flocculant is designated as VAC-D1.

[0045] Comparative Example 2: ((Al+Fe): Si is too low) Compared with Example 1, Comparative Example 2 differs in that the activation pH of 3.5 remains unchanged in step (3), the aluminum-iron molar ratio Al:Fe = 2 remains unchanged, and only the molar ratio of metal elements to silicon is adjusted to (Al+Fe):Si = 8:1. The remaining preparation steps are exactly the same as in Example 1, and the resulting flocculant is denoted as VAC-D2.

[0046] Comparative Example 3: ((Al+Fe): Si is too high) Compared with Example 1, Comparative Example 3 differs in that the activation pH of 3.5 remains unchanged in step (3), the aluminum-iron molar ratio Al:Fe = 2 remains unchanged, and only the molar ratio of the metal element to silicon is adjusted to (Al+Fe):Si = 16:1. The remaining preparation steps are exactly the same as in Example 1, and the resulting flocculant is denoted as VAC-D3.

[0047] Comparative Examples 1-3 were tested under the exact same conditions and methods as Example 1, with a flocculant dosage of 30 mg / L and a water pH of 7.5. The test results are detailed in Table 3.

[0048] Table 3. Comparison of removal effects between Example 1 and Comparative Examples 1-3 (dosage 30 mg / L, pH=7.5) Table 3 shows that omitting dialysis purification in Comparative Example 1 leads to a sharp deterioration in performance. This is because byproducts interfere with the condensation reaction: a large amount of small molecule byproducts such as methanol produced by the hydrolysis of TPODAC remain, competing with silanol groups for metal ions and hindering the formation of Si-O-Al / Si-O-Fe bonds, thus preventing the normal construction of the organic-inorganic hybrid structure. Inaccurate pH control: byproducts alter the dielectric constant and ionic strength of the solution, affecting the accuracy of pH control and leading to Al… 3+ Fe3+ Hydrolysis produces low-activity precipitates instead of highly active polynuclear hydroxyl complexes. The active ingredients are lacking: the content of the truly flocculating silicon-aluminum-iron complex in the final product is significantly reduced, and charge neutralization, hydrophobic interactions, quaternary ammonium group interactions, and netting / sweeping abilities are all severely insufficient. This comparative example fully demonstrates that dialysis purification is a key technical feature for ensuring the structural integrity and excellent performance of composite flocculants.

[0049] A comparison of Example 2 and Example 1 shows that although the (Al+Fe):Si ratio deviates by only 20%, the decrease in removal rate exceeds the decrease in metal ion concentration. This is because this parameter amplifies the effect through its influence on the four core mechanisms of this invention. Weakened charge neutralization capacity: The reduction in aluminum and iron ions leads to a decrease in the surface positive charge density, reducing the electrostatic attraction to negatively charged microplastics and diclofenac. Limited hydrophobic effect of long carbon chains: Insufficient metal ions result in an incomplete silicon-oxygen-metal network, reducing the effective exposure area of ​​long carbon chains and decreasing the adsorption capacity for hydrophobic microplastics. Weakened effect of quaternary ammonium groups: Quaternary ammonium groups may be shielded or unevenly distributed during the condensation reaction, reducing their electropositive contribution. Reduced netting and sweeping effect: Lower polymer molecular weight, shorter chain length, smaller floc size, and looser structure make it difficult to effectively encapsulate pollutants. These four mechanisms are coupled, leading to significant performance degradation. This comparative example demonstrates that even a small deviation of 10% can cause a significant performance decrease, reflecting the precision and non-obviousness of the parameter selection in this invention. A comparison of Example 3 and Example 1 shows that an excessively high (Al+Fe):Si ratio (>15:1) will cause free metal ions to hydrolyze and generate oligomeric precipitates, which will encapsulate long carbon chains and quaternary ammonium groups, weakening the hydrophobic effect and the ability to trap and sweep.

[0050] Furthermore, the effects of the molar ratio of Al and Fe and the pH value deviating from the optimal range in this invention are also considered. When the Al:Fe ratio deviates from 2:1, it disrupts the aluminum-iron hydrolysis equilibrium: excessive Al leads to insufficient charge neutralization, while excessive Fe results in excessively rapid hydrolysis and a reduction in active sites. Activation pH exceeding 3.0-3.5 is also problematic: at pH < 3.0, silanol condensation is hindered, preventing the construction of organic-inorganic hybrid structures; at pH > 3.5, condensation is too rapid, leading to uneven distribution of active sites and decreased capture efficiency. Therefore, the optimal parameter combination of this invention ((Al+Fe):Si = 10-15:1, Al:Fe = 1.5-2:1, pH = 3.0-3.5) is crucial for achieving the synergistic effect of the four core mechanisms.

[0051] In summary, this invention provides a composite flocculant for the simultaneous removal of microplastics and new pollutants, and its preparation method. This method involves hydrolyzing and purifying the silane coupling agent TPODAC, then activating it with aluminum and iron salts in specific proportions at pH 3.0–4.0, followed by aging to obtain the composite flocculant VAC. This method significantly improves the material's synergistic removal capacity for multiple pollutants by optimizing key parameters such as the molar ratio of metal elements (Al+Fe) to silicon (10–15:1), the aluminum-iron ratio (1.5–2:1), and the activation pH (3.0–3.5). This flocculant performs excellently under typical water pH conditions (7–8): a dosage of 10 mg / L can efficiently remove microplastics (polystyrene > 90%) and conventional pollutants (nitrogen, phosphorus > 85%); a dosage of 30 mg / L achieves removal rates exceeding 75% for various new pollutants (tetracycline, diclofenac, ibuprofen). This invention has the advantages of controllable process, wide applicability, and high removal efficiency, and is suitable for the simultaneous deep treatment of microplastics and new pollutants in water bodies.

[0052] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for the preparation of a composite flocculant for simultaneous removal of microplastics and emerging pollutants, characterized by, Includes the following steps: The silane coupling agent dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride was dissolved in a mixed solution consisting of ethanol, concentrated hydrochloric acid and deionized water to obtain a silanol active solution; The silanol active solution obtained in step (1) was subjected to dialysis to obtain a purified silanol active solution. Add an aluminum and iron metal salt solution to the purified silanol active solution obtained in step (2), and then adjust the pH of the system to 3.0~3.5 with an alkaline solution to obtain the reaction solution; The reaction solution obtained in step (3) is stirred and then allowed to stand for aging to obtain the composite flocculant.

2. The method for preparing a composite flocculant according to claim 1, characterized by, In step (1), the volume concentration of the silane coupling agent is 2%, the composition of ethanol and concentrated hydrochloric acid in the mixed solution is 78% and 0.02%, respectively, and the dissolution rate is 200-250 r / min.

3. The preparation method according to claim 1, characterized in that, In step (2), the dialysis treatment specifically involves placing the silanol active solution in the pretreated dialysis membrane and performing dialysis in a dilute hydrochloric acid solution with a pH of 2 to 2.5 for a total dialysis time of 8 to 10 hours, during which the dialysis solution is replaced 4 to 6 times.

4. The production method according to claim 3, characterized by, The pretreatment method for the dialysis membrane includes: boiling it in a 2% sodium bicarbonate solution and a 1 mmol / L EDTA solution for 8-15 minutes respectively, and then rinsing it with deionized water.

5. The preparation method according to claim 1, characterized in that, In step (3), the total amount of aluminum and iron in the metal salt solution containing aluminum and iron is 10~15:1 in molar ratio to silicon in the purified silanol active solution, and the molar ratio of aluminum to iron is 1.5~2:

1. The total concentration of metal ions in the mixed solution is controlled to be no more than 0.05 mol / L.

6. The method of claim 1, wherein, In step (3), the metal salt solutions containing aluminum and iron are aluminum chloride and ferric chloride, respectively; the alkaline solution is a sodium hydroxide solution with a concentration of 0.5 mol / L.

7. The preparation method according to claim 1, characterized in that, In step (4), the stirring reaction is magnetic stirring, with a stirring rate of 150~200 rpm, a temperature of 18~22 ℃, and a stirring time of 10~15h.

8. The method of claim 1, wherein, In step (4), the static aging temperature is 18-22 ℃ and the static time is 10-15 h to obtain the composite flocculant.

9. The preparation method according to claim 1, characterized in that, The new pollutants include diclofenac, ibuprofen, and tetracycline.

10. A composite flocculant prepared by the method according to any one of claims 1-9, characterized in that, For the synergistic removal of microplastics and conventional nutrients, the dosage of the composite flocculant is 10~20 mg / L; For enhanced removal of new pollutants, the dosage of the composite flocculant is 30-50 mg / L.